A District-Level Analysis of the Effect of Risk Exposure on the Demand for Index Insurance in Mongolia - Lukas Mogge (RWI - Leibniz-Institut für Wirtschaftsforschung, 2023)
This paper provides novel evidence on how risk exposure shapes the demand for index-based weather insurance. The focus is on Mongolia, where index insurance is offered as a commercially marketed product to pastoralists threatened by extreme weather events that cause high livestock mortality. Using a two-way fixed effect model and country-wide district-level data spanning a period of five years, this paper shows that the demand for index insurance increases in areas exposed to adverse weather conditions occurring in the months preceding the end of the insurance sales period. The effect is neither driven by the receipt of insurance payouts nor by observing peers receiving payouts. I argue that these results can be best explained by insurance purchasers adapting their risk perception in response to recent weather risks. The findings of this paper point to a problem for policymakers as a period of mild weather conditions could cause households to lose interest in purchasing insurance, thus leading to underinvestment in insurance coverage.
Keywords: O12; O13; O14; 330; Extreme weather events; index insurance; livestock; risk; Mongolia